PEMBERDAYAAN KADER KESEHATAN TENTANG PENYAKIT HIPERTENSI DALAM UPAYA PREVENTIF KASUS GAGAL GINJAL KRONIK DI DESA JAMBANGAN KECAMATAN JAMBANGAN DI KABUPATEN SIDOARJO - Bahrudin, Moch; Dari, Tanty Wulan; Maimuna, Siti; Sumiatin, Titik; Tri Ningsih, Wahyu; Su'udi, Su'udi (Universitas Kadiri, 2024)
Implementation of community service regarding hypertension in an effort to prevent cases of chronic kidney failure in Jambangan Village, Jambangan sub-district, Sidoarjo district for health cadres which was carried out in April-July 2024, which was attended by 46 health cadre mothers. which began with singing the song Indonesia Raya. Which was continued with remarks from the Village Head and followed by remarks from Mrs. Tanty Wulan Dari, S.Kep, Ns, M.Kes. The service method uses the empowerment of health cadres through lectures, practice and joint exercise. Before the main event, the community service team conducted a pre-test with the aim of finding out the knowledge of female health cadres about hypertension and complications of chronic kidney failure and their management for 15 minutes.